Structure based in-silico study on UDP-N-acetylmuramoyl-L-alanyl-D-glutamate-2, 6-diaminopimelate ligase (MurE) from Acinetobacter baumannii as a drug target against nosocomial infections. (2019) - Amera, Gizachew Muluneh; Khan, Rameez Jabeer; Pathak, Amita; Kumar, Ankit; Singh, Amit Kumar
Abstract: UDP- N -acetylmuramoyl-L-alanyl-d -glutamate–2, 6-diaminopimelate ligase (MurE) initiates reaction by adding meso-diaminopimelic acid to the nucleotide precursor UDP- N -acetylmuramoyl-L-alanyl-d -glutamate, during the synthesis of murein in the cytoplasm. This enzyme is crucial for microorganisms including A. baumannii, and is non-homologous to mammals; therefore, it can be used as potential antibacterial drug target. The crystallographic structure of UDP- N -acetylmuramoyl-L-alanyl-d -glutamate–l -lysine ligase (MurE) from Staphylococcus aureus with UDP-MurNAc- Ala-Glu-Lys (4C13) was used to model the tertiary structure of UDP- N -acetylmuramoyl-l -alanine-d -glutamate:meso diaminopimelate ligase (MurE) from A. baumannii . The evaluated structure of MurE was aligned on the template and nitrogen-termini, central, and carbon-termini domains were obtained (the first, second, and third domain, respectively). It has been found from the conserved region that the active site residues, Arg383, Asp407, Asn408, Arg410, and Glu463, participated in the binding site, whereas Asn408 was the vital residue involved in the catalysis during synthesis of murein in Acinetobacter baumannii, by adding meso-diaminopimelic acid to a nucleotide precursor. Consequently, disrupting the above-mentioned amino acid chain could hamper the usual role of MurE. Overall, six thousand seven hundred and twenty-five (6725) compounds were capable of binding to MurE with low binding energy. The natural ligands were screened to eliminate molecules with unwanted properties for drug-likeness on the basis of physicochemical properties. Eight (8) ligands such as ZINC15675880, ZINC15675922, ZINC15675928, ZINC15707240, ZINC15707335, ZINC15675930, ZINC20503844, and ZINC30879537 have satisfied the ADMET parameters. Out of these, two compounds that had the best binding energies and docking results were selected for molecular dynamics simulations. The results for all parameters indicated stability and less fluctuation of the complexes. Therefore, after wet-lab confirmation, these compounds could be recommended as potential drugs against Acinetobacter baumannii infections. Graphical abstract: Image 1 Highlights: A.baumannii has been identified as one of the three most important problems for human health because of multi-drug resistance. MurE from A.baumannii has a target for drug design and development, since it is crucial for the survival of the bacteria. The 3-dimensional assembly of MurE have been modeled for the first time in this bacteria. ZINC08846613 was documented to be of lowest binding energy from the aspect of enzyme inhibition. From pharmacokinetic analysis, ZINC15675880 has fulfilled all of the ADME and toxicity properties.